Triagem de cepas de Saccharomyces cerevisiae sensíveis ao metilglioxal - Pavin, Sandra Sartoretto (2015)
Methylglyoxal is a very reactive α-dicarbonilic compound, that can can be formed in high concentrations in hyperglycemic conditions. It is produced mainly via non-enzymatic ways from glycolytic intermediates, like glyceraldehyde-3-phophate and di-hydroxyketone phosphate. This compound is known for reacting with macromolecules such as proteins, DNA, and RNA, altering their funtions. However, the toxic mechanisms involved in MG toxicity on the biological systems are not fully elucidated. Thus, the present study aimed to perform a screening to identify Saccharomyces cerevisiae mutant strains sensitive to MG, using mainly strains with oxidative stress and DNA damage related mutations. Ninety-six mutant strains were placed in YPD-galactose medium containing different MG concentrations (5-12 mM). The MG sensitivity was evaluated through growth and cellular viability parameters. The different tests showed that the MG toxicity was more pronounced in strains with deletions in genes involved with DNA repair events: Rad23 and Rad50. The MG exposure also decreased markedly the growth and cellular viability in the mutant strains with deletions in genes for the enzymes glyoxalase 1 (Glo1) and glutathione (Gsh1). The results obtained highlight the importance of the glyoxalase 1 system in MG detoxification and point the DNA as a target for the toxicity of the compound in S. cerevisae.